Using O–D matrices for decision making in road network management - Alonso, Borja; Moura, José L.; Ibeas, Ángel; dell’Olio, Luigi (Transport, 2013)
This article uses a real example to demonstrate the importance of mobility modelling (objective criteria) on correctly planned investments in infrastructure. Some radical conclusions are drawn which differ greatly from those suggested by more subjective mental models. Strategic developments on inter-urban networks are evaluated by applying a mobility model including a model for estimating O–D matrices based on traffic counts and a model for the optimal location of traffic counting stations at the same time as a population accessibility model. An important decision making tool is provided for planning investments in road infrastructure by rationalising the high public spending required for this type of work. The models are applied to various possible projects at determined points on a regional road network in the Autonomous Community of Cantabria (Northern Spain) following the proposals and demands of different social and political groups. The models find a 68% reduction in the number of links required to obtain O–D matrices. This provides considerable savings in data collection costs (approximately 50% less) involving future traffic counts on similar and especially regional road networks. First Published Online: 03 Apr 2013